Imaging findings in the spine of tuberculosis infected children - Estrada-Pérez, Andrés; Quintero-Ortiz, Jorge; Uribe, Alejandro; Ortiz-Marulanda, Margarita M.; Vargas, Sergio Alberto (Revista Colombiana de Ortopedia y Traumatología, 2015)
Introduction: Tuberculosis has high incidence worldwide, 5% of cases in the spine, of which 30% are children. Tuberculous spondylitis is a major problem due to the high morbidity, bone destruction and potential associated neurological impairment. Objective: The aim of this study is to describe the imaging findings in childhood spinal tuberculosis. Materials and methods: A case series study including 4 patients was performed, evaluating imaging findings in children under 13 years with vertebral tuberculosis treated at a high complexity hospital between 2008 and 2012. A specialized neuroimaging radiologist evaluated the images. Results: All patients had vertebral involvement of at least two levels. Vertebral collapse and kyphosis deformity were present in 75% of the patients. The most frequently involved segments were thoracic and lumbar, both with 75% incidence, no cases in cervical and sacral spine were found. Discussion: The weakness of the study was that only a few cases were included, however the findings were similar to those reported in worldwide medical reports. What was found shows that the diagnosis and intervention of childhood spinal tuberculosis is getting late, when it is not possible to treat any different to the functional consequences. Evidence level: IV